Saint Paul's Cathedral - Wren, Christopher
In general arrangement, the rebuilt St. Paul's was Gothic and traditional. The detail was Greek, the rounded arches Romanesque, and the dome Eastern. Within, the arcading of the nave and choir is arranged in rectangular bays divided by Corinthian pilasters supporting a giant cornice at what-in Gothic terms-would be called the triforium stage. Above, each bay is lit by a single clerestory window and covered with a shallow, decorated dome vault. The aisles are similarly covered with flat domes richly decorated and gilded. Structural support to these massive surfaces is given by buttresses concealed behind a curtain wall with fake windows in the exterior facade, and is clearly based on medieval practices. Wren's uncle, Matthew, was Bishop of Ely from 1638 to 1667, and it may well be that the structural decisions, especially that of support of the dome, derived from the Octagon of Ely Cathedral. But there is nothing medieval about the classical columns of this great space, which was completetd within the lifetime and under the constant supervision of Wren.